Selective serotonin re‐uptake inhibiting antidepressants and the risk of overanticoagulation during acenocoumarol maintenance treatment - Teichert, Martina; Visser, Loes E.; Uitterlinden, Andrė G.; Hofman, Albert; Buhre, Peter J.; Straus, Sabine; De Smet, Peter A. G. M.; Stricker, Bruno HCh (British journal of clinical pharmacology, 2011)
WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT • Coumarin anticoagulants and selective serotonin re‐uptake inhibitors (SSRIs) have been reported to cause bleeding. Combination of these drug groups might enhance this risk. Case reports showed an increase of prothrombin time for the combination of warfarin with fluvoxamine and fluoxetine. This has not yet been confirmed by population based studies. WHAT THIS STUDY ADDS • Fluvoxamine and venlafaxine increased prothrombin time in users of acenocoumarol above a critical value which is associated with an increased bleeding risk. The other SSRIs had no influence on acenocoumarol effectiveness, however numbers of drug users were low. The combination of fluvoxamine and venlafaxine with acenocoumarol should be monitored by measurements of the international normalized ratio to avoid overanticoagulation. AIM The aim of this study was to investigate the effects of co‐medication with selective serotonin re‐uptake inhibitors (SSRIs) on overanticoagulation during acenocoumarol maintenance treatment. METHODS All subjects from The Rotterdam Study who received acenocoumarol maintenance treatment between April 1 1991 and September 9 2009 were followed for the event of an international normalized ratio (INR) ≥6, until death, end of treatment or end of the study period. With the Andersen‐Gill extension of the Cox proportional hazards model, risks for repeated events of overanticoagulation in relation to concomitant SSRI use were calculated. RESULTS The risk for overanticoagulation during acenocoumarol maintenance treatment was increased in combination with fluvoxamine (HR 2.63, 95% CI 1.49, 4.66) and venlafaxine (HR 2.19, 95% CI 1.21, 3.99). There was no increase in risk for the other SSRIs, but numbers of exposed cases were low for all SSRIs except paroxetine. CONCLUSION Fluvoxamine and venlafaxine were associated with a more than double risk of INR values ≥6 in acenocoumarol treated subjects.